The Meaning of Communication of Andun Dance Performances in the Serawai Tribe Community (Case Study in the Implementation of Andun Dance in Suka Negeri Village, Air Nipis District, South Bengkulu Regency) - Lena Alfa Rhoza (Al-Makki Publisher, 2025)
This study aims to examine the communication meaning of the Andun Dance performance within the Serawai ethnic community. A qualitative method with a case study approach was employed to explore the communication aspects of the Andun Dance in this cultural context. The research is grounded in the symbolic interaction theory by Herbert Blumer. Data were collected through observation, interviews, and documentation.The findings reveal that the Andun Dance conveys a profound communication meaning and constitutes an integral part of the social and cultural life of the Serawai people. This dance is not only a form of entertainment but also serves as a representation of cultural identity, passed down from generation to generation, especially in the context of wedding ceremonies. The meaning is expressed through various nonverbal symbols, as seen in the presentation process, movement variations, and traditional costumes worn during the performance. Each element carries messages closely related to local customs, spirituality, and social relationships. The Andun Dance also symbolizes expressions of gratitude and the family's blessings to the bride and groom, as well as a symbolic farewell to their single life. According to the symbolic interaction theory, this performance reflects a cultural practice rich in symbolic meaning, shaped through consistent social interaction within the community. Therefore, the Andun Dance is not only valued for its aesthetic qualities but also holds philosophical and spiritual significance, reinforcing the cultural identity of the Serawai ethnic group.